Implementation of EnergyPlus Objects in SAPTool - Fernandes, Marco (2019)
In the scope of the Ren4EEnIEQ project (https://ren4eenieq.wordpress.com/) a comprehensive BIM add-on tool for the improvement of energy efficiency and indoor environment quality in renovation of buildings (SAPTool) was developed. This tool – developed in Java – allows to produce alternative building geometries, from the same user requirements and preferences, and then evaluate their energy performance using dynamic simulation. The latter is performed by the coupled simulation engine EnergyPlus. This manual describes the implementation methodology of selected EnergyPlus objects in the SAPTool – internal gains, HVAC systems, DHW and water systems, air contaminants, daylighting controls, window shading, and electric generation systems – and how to generate the corresponding outputs. These objects properties are mainly defined in a specific database (SAPTool_SQLite database) and their simulation is performed with the EnergyPlus engine (version 9.2). Refer to the EnergyPlus Input-Output Reference for additional details on each EnergyPlus object (available in https://bigladdersoftware.com/epx/docs/9-2/input-output- reference/).